Thailand : Financial Sector Assessment Program-Detailed Assessment of Observance-Insurance Core Principles. (IMF Staff Country Reports; Country Report, 2019)
This Detailed Assessment of Observance on Insurance Core Principles on Thailand discusses that the government of Thailand has made a concerted effort to develop the insurance sector. The government has implemented a series of insurance development plans toward this end. Some significant regulatory and supervisory challenges remain, however, if Thailand is to continue to meet the pressures of a changing market and to continue to build the trust on which future growth depends. Consideration should be given to vesting more supervisory authority for key supervisory decisions with the Commission rather than with the Minister and Cabinet. Vesting authority with the Commission will help to ensure that the insurance supervisor has adequate powers to meet the objectives of insurance supervision. With respect to winding up and exit from the market, the insurance legislation should be amended to clearly establish a point at which it is no longer permissible for a troubled insurer to continue in business.